Development of a Simple, Movable, Indoor Soil Bin Equipped with some Novel Measuring and Soil Preparation Devices - Oyebode, O.; Shoji, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Challenged by the complexities involved in constructing a standard indoor soil bin, and the difficulties in taking certain measurements before, during and after soil bin experiments, a simple soil bin was developed. The soil bin was mainly made with wooden slabs and angle irons. it was equipped with a digitized, mechanically operated cone penetrometer, a sinkage measurement system as well as a stepless soil leveler. An existing manually operated ASABE standard penetrometer was digitized using strain gauges fixed on the penetrometer ring for force measurements and a distance meter for concurrent depth measurement. The penetrometer was operated by a 90 W linear motor with a switch located outside the soil bin thereby making it possible to measure cone index at constant speed in a perfectly vertical direction. The calibration of the strain gauges and the distance meter showed good linearity (R2>0.997). A stepless levelling device that allows for seamless vertical adjustment of soil height was developed. Soil surfaces levelled with this device had an average coefficient of variation of 0.040 compared with that of 0.080 achieved from carefully manually levelled soil beds. Soil compaction and compaction uniformity experiment was done using sandy clay loam soil which was compacted with a 27 cm diameter steel roller weighing 103 kg/m. Two ultrasonic range finders mounted at the front and rear of the compactor cart automatically measured the sinkage of the soil surface after the compaction. The sinkage on the soil surface and the uniformity in cone index were significantly affected by the number of layers and roller passages and compaction uniformity increases with increase in the number of soil layers. Therefore, the accuracy of the measuring systems and the structural stability of the various components of the soil bin indicate that they are suitable for experiments.